Analysis of the factors affecting the poverty in rural areas around gold mine areas in West Sumbawa Regency - I Ibrahim; M Baiquni; S Ritohardoyo; S Setiadi (Journal of Degraded and Mining Lands Management, 2016)
West Sumbawa Regencyis one of the regencies that are rich of natural resources managed by PT. Newmont Nusa Tenggara. However, local communities around the gold mine areas have generally to date been poor. This study was aimed to (1) examine the effect of material poverty, physical weakness, isolation, vulnerability, and powerlessness on poverty, and (2) describe the distribution of rural povertybased on land slope mapsin gold mine areas in West Sumbawa Regency.This study applied a survey technique, observation, and structured interviews to collect data. The processing and analysis of data was carried out by a quantitative method using a multiple regression analysis. The results of the study showed that the factors significantly affecting the poverty among rural communities around gold mine areas were material poverty, physical weakness, isolation, vulnerability and powerlessness (R2 = 0.715). However, the mostly dominant factor affecting the poverty was powerlessness (t = 19.715). Meanwhile, the distribution of poverty based on topographic sites showed that the poverty occurred in villages with plain topography (Goa Village), terrain topography (Maluk Village), wave topography (Belo Village), and hilly topography (Sekongkang Bawah Village). The poverties occurred in all the villages were mostly affected by powerlessness with t values of 3.489, 13.921, 11.828, and 6.504, respectively. This condition was due to minimum access and communication by local communities to local government and the gold mining company of PT. Newmont Nusa Tenggara